Ten principles for effective AR4D programs - Vermeulen, Sonja J.; Campbell, Bruce M. (2015)
Effective agricultural research for development (AR4D) faces many challenges that are exacerbated under climate change. Effective behaviours by AR4D programs may drive the likelihood and quality of positive outcomes when working with partners.Explicit principles about effective behaviours can improve AR4D theories of change and enhance achievement of outcomes. Internal learning over four years of CCAFS implementation suggests ten principles to guide the program and explore which behaviours are most effective.